Bacterial calcification in infective endocarditis. Issue 767 (September 1989) - Poller, D. N.; Curry, A.; Ganguli, L. A.; Routledge, R. C.
Abstract : The present report is the first description to our knowledge of a clinical case of bacterial calcification in human infective endocarditic vegetations. Partial calcification of bacteria within vegetations may be a further mechanism of bacterial protection from host defences and antibiotics. Similar calcification has recently been reported in vegetations formed on porcine valvular prostheses implanted experimentally in sheep.